Roles and regulation of histone acetylation in hepatocellular carcinoma - Xia, Jin-kun; Qin, Xue-qian; Zhang, Lu; Liu, Shu-jun; Shi, Xiao-lei; Ren, Hao-zhen (Frontiers in Genetics, 2022)
Hepatocellular Carcinoma (HCC) is the most frequent malignant tumor of the liver, but its prognosis is poor. Histone acetylation is an important epigenetic regulatory mode that modulates chromatin structure and transcriptional status to control gene expression in eukaryotic cells. Generally, histone acetylation and deacetylation processes are controlled by the opposing activities of histone acetyltransferases (HATs) and histone deacetylases (HDACs). Dysregulation of histone modification is reported to drive aberrant transcriptional programmes that facilitate liver cancer onset and progression. Emerging studies have demonstrated that several HDAC inhibitors exert tumor-suppressive properties via activation of various cell death molecular pathways in HCC. However, the complexity involved in the epigenetic transcription modifications and non-epigenetic cellular signaling processes limit their potential clinical applications. This review brings an in-depth view of the oncogenic mechanisms reported to be related to aberrant HCC-associated histone acetylation, which might provide new insights into the effective therapeutic strategies to prevent and treat HCC.